Assisting students with conduct disorders in Gweru urban primary schools: issues and challenges - Gudyanga, Ephias; Nyamande, W.S.; Wadesango, N. (Kamla-Raj, 2016)
The study intended to establish the role played by the Schools’ Psychological Services (SPS) in counseling children with conduct disorders (CDs) in Gweru Urban Primary Schools. The descriptive design was employed in this study. The sample was drawn from five primary schools in the district. Random sampling was used to select one school from each of the five cluster/ zones in Gweru Urban District. The questionnaire and interview schedule were used to elicit data from the respondents. Descriptive statistics were used to analyses the data collected. The main findings revealed that the role of Education Psychologists (E.P) and Education Officers (E.O) guidance and counseling in counseling children with (CDs) in primary schools is not clearly defined. Heads and teachers are not aware of the role played by these SPS personnel in counseling children. The SPS personnel are recommended to staff develop heads and teachers on the role of SPS in counseling children in primary schools. The SPS should systematically provide technical support to heads and teachers in counseling children with CDs. The SPS should systematically provide technical support to heads and teachers in counseling children with conduct disorders in primary schools.